Type I Shapovalov wave spacetimes in the Brans-Dicke scalar-tensor theory of gravity - Osetrin, Konstantin E. (Symmetry)
Exact solutions for Shapovalov wave spacetimes of type I in Brans-Dicke's scalar-tensor theory of gravity are constructed. Shapovalov wave spacetimes describe gravitational wave models that allow for the the separation of wave variables in privileged coordinate systems. In contrast to general relativity, the vacuum field equations of the Brans-Dicke scalar-tensor theory of gravity lead to exact solutions for type I Shapovalov spaces, allowing for the the construction of observational tests to detect such wave disturbances. Furthermore, the equations for the trajectories of the test particles are obtained for the models considered.